Cloud Computing based Intelligent Bank Locker System. Issue 1 (January 2021) - Devi, A.; Julie Therese, M.; Premalatha, G.
Abstract: Now a day's personal security is a major concern in all the aspects. Most of the people have their personal asserts such as cash, gold, silver etc, in a locker due to security of the accessories. But the security of those asserts is not assured because of robbery and theft problem happening in day today life. In order to overcome the drawback, we proposed a system based on Cloud computing for providing and ensuring high security in the bank, Jewellery shop, home and every place where security of the locker is more important. The proposed system consists of wireless switch, Raspberry pi 3, GSM and finger print scanner in order to allow only authenticated customer to open their lockers to take their accessories. If the authentication fails, the GSM automatically sends the message to the customer regarding failure of locker opening, and gives the alarm signal that makes the people in the bank to notice.